Iraqi postage stamp commemorating the 6th Annual Arab Petroleum Congress, Baghdad (1967)
Depicts oil derrick, pipeline, and emblem of the 6th Annual Arab Petroleum Congress held in Baghdad, Iraq in March 1967.
Keywords: Postage stamps; Petroleum--Congresses; Commemorative postage stamps; Iraq--Baghdad; Science on postage stamps; Thomas De La Rue & Company; Congresses and conventions; Arab Petroleum Congress; Iraq